If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4g + 9 = 13 Reorder the terms: 9 + 4g = 13 Solving 9 + 4g = 13 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 4g = 13 + -9 Combine like terms: 9 + -9 = 0 0 + 4g = 13 + -9 4g = 13 + -9 Combine like terms: 13 + -9 = 4 4g = 4 Divide each side by '4'. g = 1 Simplifying g = 1
| 2(x+1)+3x=37 | | 4x-3+5x=6x-3+3x | | x/3+4=37 | | 4.8d=1.3d-21 | | 2(x+1)+3x=27 | | x/8=12/32 | | 2+4y=6 | | 2(x+1)3x=37 | | 2x-5=36 | | p^3+2p^2-4p-8=0 | | 9x-7=4x-7+5x | | m/-6=8 | | 4f+7=9 | | (3x+2)2+(4x-3)2=(5x-1)2 | | 6x^3+x^2+x=0 | | 6x^2+19x+7=-1 | | r-5.4=9.2 | | 9-n/3=28 | | 3x-5=4x+9 | | 100x^4+399x^2-4=0 | | 3(x+6)=3x+18 | | 11=2g-5 | | 876-4x=14x+19 | | 5-9x=190-44x | | -6w+18=20w | | 7=t-6-3 | | 3(m-3)+7(m+3)=16-4(7-m) | | 2x+3=4(x-1)+3 | | X^2-12x+36(x-6)=27(x-8) | | X+1+x=2+2x-1 | | 6k-3=-15 | | 7(x-4)-3=46 |